Uso del espacio y fidelidad de sitio entre hembras y machos adultos de monos araña de vientre blanco (Ateles belzebuth) en la Amazonía Ecuatoriana (2021)
During the last decades, multiple studies about the social system and behavior of spider monkeys(genus Ateles)have been published. These primates are part of the species with a high degree of fission-fusion dynamics (members of the same group can associate and separate), and therefore, they can differ in the use of the space inside their home range. Spider monkeys are segregated by sex, it means that the use of space is different between females and males. In this study, we used a dataset of a group of white-bellied spider monkeys (Ateles belzebuth) colected at the Tiputini Biodiversity Station, in Ecuador. The spatial data obtained were used to estimate the home ranges and core areas of the adult females and males of the group throught Local Convex Hull method. We found significant differences in the annual use of space between females and males and, in both cases, there is a greater variation...